Should police identities be disclosed in anti-riot operations transpiring in Cyprus?: a juxtaposition of novice and senior police constables’ perceptions - Constantinou, Angelo G. (European journal on criminal policy and research, 2021)
The article sets out to examine the stances of novice and senior Cypriot law enforcers towards the disclosure of their identities in anti-riot operations. For doing so, the input of 201 Cypriot law enforcers into a two-phase cross-sectional study is examined. Unsurprisingly, it is demonstrated that, although by rendering police officers identifiable during crowd controls will unquestionably enhance police legitimacy, senior law enforcers oppose such development (regardless of their gender, rank, length of service, post, and experience). However, this is not reflected in the perceptions of police cadets, whose (only) 1-year service at the police seems to prevent them from following in the footsteps of their senior colleagues. To this end, particular aspects of police culture could have a substantive role in supressing procedural justice, that is transparency and justice in identifying deviant police officers during anti-riot operations.